Pengaruh Konten Youtube Picky Picks terhadap Sikap Mahasiswa KPI UIN Imam Bonjol Padang - Arief Fadhil Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Picky Picks Youtube content is one of the most popular Youtube channel that is in demand among young people, especially collage, while this content has a harmful impact on the audience, because it tends to use dirty language, display images containing pornographic elements and bad behavior ini everyday life. The focus of this paper is to see whther there is an effect of Picky Picks Youtube content on the attitudes of Islamic Broadcasting Comunication students at UIN Imam Bonjol Padang class of 2016-2018. The research method in this study uses the type of explanative correlation research with a quantitative approach. This method connects or looks for cause and effect between two variables or more concepts (variabes) to be studied. The results showed that the influence of Picky Picks Youtube content had a major effect on the attitudes of KPI collage at UIN Imam Bonjol Padang generation of 2016-2018. This is shown from the significant (partial) cognitive, affective and conative values of 0.000 < 0.05, Meand free variables affect signifish indifferently to bound variables.